Identification and Experimental Validation of Biomarkers Related to MiR-125a-5p in Chronic Obstructive Pulmonary Disease - Jing X; Li Y (International Journal of COPD)
Xia Jing, Yueqin Li Department of General Medical, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Third Hospital of Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of ChinaCorrespondence: Yueqin Li, Department of General Medical, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Third Hospital of Shanxi Medical University, Taiyuan, Shanxi, 030000, People’s Republic of China, Email 13934571745@163.comPurpose: The miR-125a-5p has been reported influence the development of lung cancer, however, the link between it and chronic obstructive pulmonary disease (COPD) is still not well understood. Hence, this study was designed to investigate the molecular pathway by which miR-125a-5p related biomarkers were involved in COPD.Patients and Methods: The differentially expressed genes (DEGs) and module genes related to COPD in GSE100153 were screened out by differential analysis and weighted gene co-expression network analysis, respectively. Then, the target genes of miR-125a-5p obtained from miRWalk database were intersected with DEGs and module genes, followed by identification of biomarkers through SVM-RFE algorithms. Moreover, the gene set enrichment analysis, immune infiltration analysis, construction of regulatory network, single-cell analysis and Mendelian randomization (MR) analysis were performed. At last, the expression levels of the biomarkers were further validated in GSE100153 and GSE146560 as well as in qRT-PCR.Results: A total of 10 genes were acquired by intersecting the 126 DEGs, the 3989 module genes, and 2329 target genes, of which PITHD1, CNTNAP2 and GUCD1 were identified as biomarkers. Enrichment analysis showed their roles in various cellular functions. In addition, significant associations were identified between 9 distinct cells and biomarkers. Subsequently, 5 TFs and 63 therapeutic agents were predicted as biomarkers. Moreover, GUCD1 and PITHD1 were significantly different between case and control in T cells and Alveolar cells. In COPD, GUCD1 and PITHD1 were significantly down-regulated in GSE100153 and GSE146560 datasets and confirmed by qRT-PCR.Conclusion: In our study, PITHD1, CNTNAP2, and GUCD1 were recognized as biomarkers related to miR-125a-5p-related genes in COPD, providing new references for treatment of COPD.Keywords: drug prediction, immune infiltration analysis, MiR-125a-5p, single-cell analysis